GAMBARAN CAREER ADAPTABILITY PADA KARYAWAN DI JABODETABEK - Putri, Anastasya Ananta; Ronauli, Puji Tania (Atma Jaya Catholic University of Indonesia, 2024)
Career adaptability has become a crucial topic, particularly for young people navigating dynamic market changes and workplace challenges while pursuing their dream jobs. These factors heavily influence how individuals plan and build their careers, underscoring the importance of career adaptability—an individual's capacity to manage current and future tasks, job role changes, and transitions at work, all of which significantly affect their lives. This study examined the career adaptability of 307 employees aged 17–60 in the Jabodetabek area using a quantitative approach and descriptive analysis. Data were collected with the Career Adapt-Abilities Scale Indonesian Form (CAAS-Indonesian Form). The results indicated that the four dimensions of career adaptability—concern, control, curiosity, and confidence—were at moderate levels. Additionally, a positive correlation was observed between career adaptability and job satisfaction. Future research should explore the relationship between job satisfaction and career adaptability in greater detail.